Дворянский род Арандаренко в европейской истории - Борошко, С.Л.; Борошко, Л.В. (Сіверщина в історії України, 2021)
Впервые предоставлен подробный генеалогический обзор дворянского рода Арандаренко. Приводятся данные о его древнем польском
шляхетском происхождении от рода Яранда Брудзевского герба Помян.
Анализируется процесс интеграции его представителей сначала в среду казацкой старшины Гетманщины, а позже – дворянства Российской
империи. Выделено пять ветвей дворянского рода Арандаренко с последующей краткой биографической характеристикой наиболее известных
их представителей. Отдельное внимание в статье отведено вопросу
родственных связей дворянского рода Арандаренко с другими знатными родами, особенно немецкими. Реконструируются основные этапы развития рода Арандаренко, в том числе и после революции 1917 г. For the first time, a detailed overview of the Cossack foremen of the Arandarenko
family is provided. The article provides data on his ancient Polish gentry origin from
the Yaranda clan of the Brudze coat of arms of Pomyan, about his Zaporozhye ancestors
whose famous representatives were the Cossack hetman Timofey Arandarenko.
The division of the descendants of Yarand Brudzewski into several branches - nobles,
clergymen and ordinary Cossacks - is considered, with an analysis of the historical
change of the surname and its variability. The chronological stages in the development
of the Arandarenko clan, its unification through marriages with the ancient noble families
of the Prussian and Ostsee Germans are given. Studied five sons of the cornet Ivan
Arandarenko, as five ancestors of separate noble families of Arandarenko. The historical
reintegration of individual representatives of Europe is considered as the historical
homeland of the Arandarenko clan. The data on the fate of individual representatives
of the Arandarnko clan after the Bolshevik revolution of 1917 are presented.